Combining Stocks and Flows of Knowledge: The Effects of Intra‐Functional and Cross‐Functional Complementarity. (15th October 2013) - Ambos, Tina C.; Nell, Phillip C.; Pedersen, Torben
<x xml:space="preserve">Abstract</x> While previous research has mostly focused on either knowledge stocks or knowledge flows, our study is among the first to integrate these perspectives in order to shed light on the complementarity effects of different types of knowledge stocks and flows in the multinational corporation (MNC). This study investigates intra‐functional as well as cross‐functional complementarity effects from the perspective of the knowledge recipient and tests their impact on the benefit created for MNC units. Based on a comprehensive sample of 324 relationships between MNC units, we find that both types of complementarity create benefits for these units, but that the effects from intra‐functional combinations of knowledge stocks and flows are significantly stronger than from cross‐functional combinations.